Signifikansi Antara Regulasi Pandemi Covid-19 dan Iklim Organisasi dengan Pelayanan Prima sebagai Intervening terhadap Produktivitas Pendidikan Sekolah Menengah Kejuruan di Kabupaten Bogor - Deswita Deswita; Lubban Anwari Alhamidi (Neolectura, 2021)
This study aims to determine the relationship between organizational climate and the Covid-19 pandemic with excellent service as an intervening on the productivity of vocational high school education in Bogor Regency. The method used in this study is a quantitative research method. The sampling technique in this study used a purposive sampling technique involving 100 educational activists such as educators, students, vice principals to principals at 20 public and private vocational high schools in Bogor Regency. The instruments used in this research are the organizational climate scale, the Covid-19 pandemic and the excellent service scale and the education productivity scale. Analysis of the data used is analysis. The analysis test in this study will test normality, linearity, and simple regression using intervening or path analysis. The correlation coefficient value generated based on the analysis of the results that have been carried out shows the significance value of Variable X1 (Organizational Climate) of 1.00 greater than 0.05 and X2 (Covid-19 Pandemic Regulations) and Variable Z (Excellent Service) of 0.000 more smaller than 0.05. This means that X1 has no significant effect on the Y variable (Vocational High School Productivity) while the X2 and Z variables have a significant effect on the Y variable (Vocational Productivity).